THE EFFECT OF USING ROUND TABLE TECHNIQUE ON STUDENT’S ABILITY IN WRITING DESCRIPTIVE TEXT AT TENTH GRADE OF SMA DAERAH SEI BEJANGKAR IN ACADEMIC YEAR 2021/2022 - Supiatman, Lis; Ayu Ningsih, Sri; Aryni, Yen (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The purpose of this research was to determine whether there was an effect of using the Round Table Technique on Student’s ability in writing descriptive text at Tenth Grade of SMA Daerah Sei Bejangkar in Academic Year 2021/2022. This research used a quantitative approach, and used quasi experimental design. The research used two classes, namely the experimental group and the control group. The population of tenth grade SMA Daerah Sei Bejangkar were 84 students. The sampling technique used was simple random sampling and the samples were all students at tenth grade of SMA Daerah Sei Bejangkar. This research used two classes, namely the experimental group and the control group. The experimental group consisted of 42 students and the control group consisted of 42 students. The experimental group was taught by applying the round table technique and the control group was taught using the conventional technique. In addition, this research was carried out through the following procedures: giving pre-test, applying treatment and giving post- test. The results obtained from the research prove that the score of experimental group was higher than control group of students’ ability in writing descriptive text. Based on the calculation of the t-test is the score of product moment degree of freedom(df) N1+N2-2 or 42+42-2 = 82, the critical value of the t-table with a significant 0.05 is 1.66 and the t-test is 3.024. The writer concludes that t-test > t-table. Ho is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of using the Round Table Technique on students' ability in writing descriptive text at Tenth Grade of SMA Daerah Sei Bejangkar in Academic Year 2021/2022.